Assistive technologies and other supports for people with brain impairment - Scherer, Marcia J. (Marcia Joslyn), 1948- (Springer Pub. Co., 2012)
Integrating current research with the experiences of people with cognitive disabilities, this volume examines how assistive and cognitive support technologies are being harnessed to provide assistance for thinking, remembering, and learning. The book vividly describes real-life situations in which cognitively impaired individuals use assistive supports and the advantages and limitations these individuals perceive from their use. It provides information on how cognitively impaired individuals and their families and caregivers can select the most appropriate technologies from a wide array of acc.